Zn-MOFs containing flexible α, ω-alkane (or alkene)-dicarboxylates with 1, 2-bis(4-pyridyl)ethylene: comparison with Zn-MOFs containing 1, 2-bis(4-pyridyl)ethane ligands. Issue 1 (30th November 2016) - Kim, Hyun-Chul; Huh, Seong; Kim, Jin Yeong; Moon, Hoi Ri; Lee, Do Nam; Kim, Youngmee
Abstract : Four flexible α, ω-alkane (or alkene)-dicarboxylates generated Zn-MOFs with 1, 2-bis(4-pyridyl)ethylene pillars; the diamond-like MOF with muconate exhibits good CO2 sorption selectivity. Abstract : Flexible ditopic α, ω-alkane (or alkene)-dicarboxylate bridging ligands provided the following six Zn-MOFs with a 1, 2-bis(4-pyridyl)ethylene (bpe) pillar (malonate (1 -bpe ), succinate (2 -bpe ), fumarate (3 -bpe ), glutarate (4 -bpe ), adipate (5 -bpe ), and muconate (6 -bpe )). Newly-prepared5 -bpe and6 -bpe were structurally characterized. Both3 -bpe and6 -bpe formed three-dimensional (3-D), diamond-like frameworks with a 4-connected uninodal net and a Schläfli symbol of 6 6 . By contrast, 5 -bpe formed a 3-D framework of a 6-connected uninodal net with a Schläfli symbol of 4 12 ·6 3 .2 -bpe formed a 2-D framework with a 4-connected uninodal net with a Schläfli symbol of 4 4 ·6 2 .3 -bpe and6 -bpe showed potential void spaces after solvent removal. Gas sorption analysis with N2, H2, and CO2 at a suitable temperature indicated that6 -bpe was an adsorbent with selectivity for CO2 adsorption at 196 K over N2 and H2 . The CO2 uptake at 196 K was 86.68 cm 3 g −1 (3.87 mmol g −1 ).3 -bpe did not exhibit appreciable uptake levels for N2, H2, and CO2, which was possibly due to the relatively rigid nonporous activated form of the framework after solvent removal. Both3 -bpe and6 -bpe exhibited a good encapsulating ability for molecular iodine in cyclohexane. The crystal structure of I2 -containing6 -bpe_I 2 was elucidated. A comparison with Zn-MOFs containing 1, 2-bis(4-pyridyl)ethane ligands is discussed.